Potential Roles of Glucagon-Like Peptide 1 Receptor Agonists (GLP-1 RAs) in Nondiabetic Populations - Dan Xu; Ankith Nair; Charlie Sigston; Chau Ho; Jia Li; Daya Yang; Xinxue Liao; Wei Chen; Ming Kuang; Yanbing Li; Christopher Reid; Haipeng Xiao (Hindawi-Wiley, 2022)
Glucagon-like peptide 1 receptor agonists (GLP-1 RAs) have been observed in several large cardiovascular outcome trials to significantly reduce the incidence of major cardiovascular event (MACE) with type 2 diabetic patients. The clinical trials of GLP-1 RAs, including lixisenatide, exenatide, liraglutide, semaglutide, albiglutide, and dulaglutide, are associated with a significantly 14% lower risk of MACE in patients with T2DM and a history of CV disease, and with a nonsignificantly 6% lower risk in patients without history of CV disease. Some of the interpretation with GLP-1 RA trials suggested the possible role of glucagon-like peptide-1 receptor agonists (GLP-1 RAs) in primary prevention of cardiovascular diseases in nondiabetic individual, echoed by a recent editorial redefining the role of GLP-1 RAs being beyond glycaemic control. The narrative review provides an in-depth insight into GLP-1 RA use guideline in different countries and regions of the world and examines the safety and concern of GLP-1 RA use. The narrative review draws the comparison of GLP-1 RA use between diabetic and nondiabetic individual in terms of cardiovascular and metabolic benefits and points out the direction of future clinical trials of GLP-1 RAs in nondiabetic individuals. The focus of the review is on GLP-1 RAs' preventive roles in nondiabetic individuals with cardiovascular disease, chronic kidney diseases, obesity, dyslipidaemia, hypertension, nonalcoholic fatty liver diseases, polycystic ovarian syndrome (PCOS), and perioperative complications of bariatric surgery, albeit in small studies and subset analysis of clinical trials of diabetic patients.